2016
DOI: 10.1080/10717544.2016.1209796
|View full text |Cite
|
Sign up to set email alerts
|

pH responsive cylindrical MSN for oral delivery of insulin-design, fabrication and evaluation

Abstract: Objective: The objective of the present study was to develop novel PMV [poly (methacrylic acidco-vinyl triethoxylsilane)]-coated mesoporous silica nanoparticles (MSN) with improved hypoglycemic effect for oral insulin (INS) delivery. Methods: MSN was synthesized under acidic condition using Pluronic Õ P 123 and Tetra ethoxy orthosilane. Surfactant was removed by calcination. Calcined MSN was coated with pH sensitive polymer PMV. Cytotoxicity of this coated MSN was evaluated by MTT assay using CHO-K1 cell line.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 41 publications
(39 reference statements)
0
26
0
Order By: Relevance
“…The inhibition of the reduction of dihydrofolate to tetrahydrofolate causes blocking of the DNA synthesis. 29,30 However, studies exploring the multifunctional nanosystems composed of mesoporous silica, hydroxyapatite, TEGDMA, MAA, and copper ions with methotrexate loading that was proposed in this study, were not found in the literature. 27 Although high-dose MTX is frequently used in the treatment, conventional dose therapy is ineffective.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The inhibition of the reduction of dihydrofolate to tetrahydrofolate causes blocking of the DNA synthesis. 29,30 However, studies exploring the multifunctional nanosystems composed of mesoporous silica, hydroxyapatite, TEGDMA, MAA, and copper ions with methotrexate loading that was proposed in this study, were not found in the literature. 27 Although high-dose MTX is frequently used in the treatment, conventional dose therapy is ineffective.…”
Section: Introductionmentioning
confidence: 83%
“…The MAA polymer has been the object of several studies of pH-sensitive functionalized nanoparticles and has also been found in applications coupled with mesoporous silica. 29,30 However, studies exploring the multifunctional nanosystems composed of mesoporous silica, hydroxyapatite, TEGDMA, MAA, and copper ions with methotrexate loading that was proposed in this study, were not found in the literature. Our results indicate that functionalized Cu-MSN/ HA nanocomposite are promising for biomedical applications especially as pH-sensitive nanocarriers for tumor-targeted drug delivery.…”
Section: Introductionmentioning
confidence: 83%
“…To solve these problems, we added Pluronic ® P123 to PCL. Pluronic compounds are widely used in the biomedical field for purposes ranging from drug delivery to medical imaging (Guha et al., 2016 ; Forget et al., 2017 ; Liu et al., 2017 ). Pluronic P123 can be added to PCL as a nucleating agent to enhance drug release.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have shown to enable improvement or added functionality of previous compounds and could also have potential in the development of super generics [ 32 ]. Such studies showing improved delivery and usability of poorly soluble, poorly permeable, very potent APIs [ 33 ], biomolecules [ 34 ], proteins [ 35 ], peptides [ 36 ], antibodies [ 37 ], and genes [ 38 ] have been published to date.…”
Section: Introductionmentioning
confidence: 99%